Use of the Bichat fat ball flap for immediate closure of surgical defects in the palate. Report of two cases - Hilber, Ezequiel Matias (2021)
The objective was to describe the use of the Bichat fat ball flap in the closure of palatal defects immediately after surgical resection. Clinical cases: clinical case number 1 (60-year-old man) presented to the consultation with an increase in volume of the soft palate mucosa, ovoid in shape, not painful on palpation, similar coloration of the palate mucosa, of 3 cm in diameter and 4 months of evolution that makes it uncomfortable to talk and feed. Clinical case number 2 (a 61-year-old man) attended the consultation with a lesion in the upper jaw at the level of the palate with a pathological diagnosis of pleomorphic adenoma. In both cases, tumor resection and immediate reconstruction were performed using a Bichat fat ball. The defects were covered only by the adipose tissue mentioned, generating a restitution ad integrum of the oral mucosa, they evolved favorably, without postoperative complications and recovering the masticatory function in a few weeks. The Bichat adipose ball flap should be considered an alternative for the repair of postsurgical defects thanks to its proximity, availability, plasticity and excellent vascularization, thus avoiding possible sequelae related to secondary healing.